Reduced visual surround suppression in schizophrenia shown by measuring contrast detection thresholds - Serrano-Pedraza, Ignacio; Romero-Ferreiro, Verónica; Read, Jenny C. A.; Diéguez-Risco, Teresa; Bagney, Alexandra; Caballero-González, Montserrat; Rodríguez-Torresano, Javier; Rodriguez-Jimenez, Roberto (Frontiers in Psychology, 2014)
Visual perception in schizophrenia is attracting a broad interest given the deep knowledge that we have about the visual system in healthy populations. One example is the class of effects known collectively as visual surround suppression. For example, the visibility of a grating located in the visual periphery is impaired by the presence of a surrounding grating of the same spatial frequency and orientation. Previous studies have suggested abnormal visual surround suppression in patients with schizophrenia. Given that schizophrenia patients have cortical alterations including hypofunction of NMDA receptors and reduced concentration of GABA neurotransmitter, which affect lateral inhibitory connections, then they should be relatively better than controls at detecting visual stimuli that are usually suppressed. We tested this hypothesis by measuring contrast detection thresholds using a new stimulus configuration. We tested two groups: 21 schizophrenia patients and 24 healthy subjects. Thresholds were obtained using Bayesian staircases in a four-alternative forced-choice detection task where the target was a grating within a 3∘ Butterworth window that appeared in one of four possible positions at 5∘ eccentricity. We compared three conditions, (a) target with no-surround, (b) target embedded within a surrounding grating of 20∘ diameter and 25% contrast with same spatial frequency and orthogonal orientation, and (c) target embedded within a surrounding grating with parallel (same) orientation. Previous results with healthy populations have shown that contrast thresholds are lower for orthogonal and no-surround (NS) conditions than for parallel surround (PS). The log-ratios between parallel and NS thresholds are used as an index quantifying visual surround suppression. Patients performed poorly compared to controls in the NS and orthogonal-surround conditions. However, they performed as well as controls when the surround was parallel, resulting in significantly lower suppression indices in patients. To examine whether the difference in suppression was driven by the lower NS thresholds for controls, we examined a matched subgroup of controls and patients, selected to have similar thresholds in the NS condition. Patients performed significantly better in the PS condition than controls. This analysis therefore indicates that a PS raised contrast thresholds less in patients than in controls. Our results support the hypothesis that inhibitory connections in early visual cortex are impaired in schizophrenia patients.